Pilot multicenter study to determine the utility of point-of-care ultrasound to predict difficulty of tracheal intubation using videolaryngoscopy with the McGrath™ Mac videolaryngoscope - Fernández-Vaquero, Miguel A.; De Luis-Cabezón, Nekari; García-Aroca, Miguel A.; Álvarez-Avello, Jose M.; Vives-Santacana, Marc; Greif, Robert; Martinez-Hurtado, Eugenio D.; Ly-Liu, Diana (Frontiers in Medicine, 2024)
Background: Clinical airway screening tests used to predict difficulties during airway management have low sensitivity and specificity. Point-of-care airway ultrasound has described measurements related to problems with difficult direct laryngoscopy. Nevertheless, the correlation between ultrasound parameters and videolaryngoscopy has not been published yet.The aim of this multicenter, prospective observational pilot study was to evaluate the applicability of clinical parameters and ultrasound measurements to find potential tracheal intubation difficulties when videolaryngoscopy is used.Methods: Preoperatively, six clinical airway assessments were performed: 1) modified Mallampati score, 2) thyromental distance, 3) sternomental distance, 4) interincisal distance, 5) upper lip bite test, and 6) neck circumference. Six ultrasound parameters were measured in awake patients: 1) distance from skin to hyoid bone, 2) distance from skin to epiglottis, 3) hyomental distance in neutral head position, 4) hyomental distance in head-extended position, 5) distance from skin to the deepest part of the palate, and 6) sagittal tongue area. And finally, there was one ultrasound measure obtained in anesthetized patients, the compressed sagittal tongue area during videolaryngoscopy. The difficulty for tracheal intubation using a McGrath™ Mac videolaryngoscope, the percentage of glottic opening, and Cormack-Lehane grade were also assessed.In this cohort of 119 subjects, tongue dimensions, particularly the sagittal tongue area, showed a robust association with increased intubation difficulty using videolaryngoscopy. A multiparametric model combining the following three ultrasound variables in awake patients: a) the distance from skin to epiglottis, b) the distance from skin to the deepest part of the palate, and c) the sagittal tongue area, yielded a sensitivity of 92.3%, specificity of 94.5%, positive predictive value of 82.8%, and negative predictive value of 97.8% (p < 0.001).Point-of-care airway ultrasound emerges as a more useful tool compared to traditional clinical scales to anticipate possible challenges during videolaryngoscopic intubation.